An experimental and numerical study of the performance monitoring of industrial pumps - 275010 Wong, Chee Keong (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1999